Two New Synonyms of Palaearctic Gelechiidae (Lepidoptera) - Bidzilya, O.V. (Вестник зоологии, 2000)
Two recent papers devoted to gelechiid-moths from France and China were critically analysed. As a result, 2 new synonyms were established.